Standards for UNiversal reporting of patient Decision Aid Evaluation studies: the development of SUNDAE Checklist. Issue 5 (21st December 2017) - Sepucha, Karen R; Abhyankar, Purva; Hoffman, Aubri S; Bekker, Hilary L; LeBlanc, Annie; Levin, Carrie A; Ropka, Mary; Shaffer, Victoria A; Sheridan, Stacey L; Stacey, Dawn; Stalmeier, Peep; Vo, Ha; et al.
Abstract : Background: Patient decision aids (PDAs) are evidence-based tools designed to help patients make specific and deliberated choices among healthcare options. The International Patient Decision Aid Standards (IPDAS) Collaboration review papers and Cochrane systematic review of PDAs have found significant gaps in the reporting of evaluations of PDAs, including poor or limited reporting of PDA content, development methods and delivery. This study sought to develop and reach consensus on reporting guidelines to improve the quality of publications evaluating PDAs. Methods: An international workgroup, consisting of members from IPDAS Collaboration, followed established methods to develop reporting guidelines for PDA evaluation studies. This paper describes the results from three completed phases: (1) planning, (2) drafting and (3) consensus, which included a modified, two-stage, online international Delphi process. The work was conducted over 2 years with bimonthly conference calls and three in-person meetings. The workgroup used input from these phases to produce a final set of recommended items in the form of a checklist. Results: The SUNDAE Checklist (Standards for UNiversal reporting of patient Decision Aid Evaluations) includes 26 items recommended for studies reporting evaluations of PDAs. In the two-stage Delphi process, 117/143 (82%) experts from 14 countries completed round 1 and 96/117 (82%) completed round 2. Respondents reached a high level of consensus on the importance of the items and indicated strong willingness to use the items when reporting PDA studies. Conclusion: The SUNDAE Checklist will help ensure that reports of PDA evaluation studies are understandable, transparent and of high quality. A separate Explanation and Elaboration publication provides additional details to support use of the checklist.